Love, money and obligation : transnational marriage in a northeastern Thai village - Lapanun, Patcharin (NUS Press, 2019)
Globalization has opened up a flow of economic and cultural exchanges. While we often think about these concepts in terms of trade policies or international treaties, they also play out in more intimate spheres, such as transnational marriages. Northeast Thailand has seen an increase in marriages between Thai women and farang (Western) men. Often the women are less well off and from rural areas in the country, while the men largely come from the United States and Europe and settle permanently in Thailand. These unions have created a new social class, with distinctive consumption patterns and lifestyles. And they are challenging gender relations and local perceptions of sexuality, marriage, and family. In Love, Money and Obligation, Patcharin Lapanun offers an exploration of these marriages and their larger effect on Thai communities. Her interviews with women and men engaging in these transnational relationships highlight the complexities of the associations, as they are shaped by love, money, and gender obligations on the one hand and the dynamics of socio-cultural and historical contexts on the other. Her in-depth and even-handed examination highlights the importance of women's agency and the strength and creativity of people seeking to forge meaningful lives in the processes of social transition and in the face of local and global encounters.